2021
DOI: 10.3390/pathogens10081020
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Clinical Isolates of Aspergillus fumigatus Induce Similar Muco-inflammatory Responses in Primary Airway Epithelial Cells

Abstract: Aspergillus is increasingly associated with lung inflammation and mucus plugging in early cystic fibrosis (CF) disease during which conidia burden is low and strains appear to be highly diverse. It is unknown whether clinical Aspergillus strains vary in their capacity to induce epithelial inflammation and mucus production. We tested the hypothesis that individual colonising strains of Aspergillus fumigatus would induce different responses. Ten paediatric CF Aspergillus isolates were compared along with two sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…A third possible interpretation is that A. fumigatus may affect CF patients differently. McLean et al investigated this hypothesis and found no variation of the mucosal and the inflammatory responses induced by different A. fumigatus clusters in different CF primary epithelial cells [34]. In the current study, clinical characteristics, serological or microbiological parameters as risk or protectable factors for lung function deterioration in CF patients colonized with A. fumigatus were assessed.…”
Section: Discussionmentioning
confidence: 74%
“…A third possible interpretation is that A. fumigatus may affect CF patients differently. McLean et al investigated this hypothesis and found no variation of the mucosal and the inflammatory responses induced by different A. fumigatus clusters in different CF primary epithelial cells [34]. In the current study, clinical characteristics, serological or microbiological parameters as risk or protectable factors for lung function deterioration in CF patients colonized with A. fumigatus were assessed.…”
Section: Discussionmentioning
confidence: 74%